1989
DOI: 10.1139/f89-110
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Sequence Similarity of Atlantic and Pacific Albacore Tuna (Thunnus alalunga)

Abstract: . 1989. Mitochondrial DNA sequence similarity of Atlantic and Pacific albacore Restriction endonuclease analysis of mitochondrial DNA purified from 1 1 south Atlantic (Capetown, South Africa) and 12 north Pacific (San Diego, USA) albacore tuna (Jhunnus alalunga) revealed no restriction sites which could distinguish an Atlantic from a Pacific albacore. Although restriction site variation was found within the pooled sample, variants were found only in single fish. These results suggest either recent isolation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 16 publications
1
22
0
1
Order By: Relevance
“…sturgeons (Brown et al, 1988) while species with low longevity also have low levels of mitochondrial DNA variation, e.g. albacore tuna (Graves and Dizon, 1989). Further research will be necessary to determine the age dependency of mitochondrial DNA before its role in any kind of population analysis can be determined (Gauldie, 1991).…”
Section: Genetic Differentiationmentioning
confidence: 99%
“…sturgeons (Brown et al, 1988) while species with low longevity also have low levels of mitochondrial DNA variation, e.g. albacore tuna (Graves and Dizon, 1989). Further research will be necessary to determine the age dependency of mitochondrial DNA before its role in any kind of population analysis can be determined (Gauldie, 1991).…”
Section: Genetic Differentiationmentioning
confidence: 99%
“…A deeper divergence among mtDNA lineages has been observed for blue marlin and sailfish (Graves and McDowell, 2003), questioning the taxonomic status of these evolutionary units. In contrast, the Atlantic and Indo-Pacific populations of tuna species such as yellowfin and skipjack were found to be genetically indistinguishable, based on a variety of molecular markers (Graves et al, 1984;Graves and Dizon, 1989;Scoles and Graves, 1993). However, Ely et al (2005) reported small differences using RFLP analysis of the mtDNA ATCO gene region for yellowfin tuna, although not for skipjack.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic similarity found in albacore Thunnus alalunga and skipjack tuna Katsuwonus pelamis between the Pacific and Atlantic Oceans by Graves et al (1984) and Graves & Dizon (1989) could be explained by their high vagility. This high migratory capacity in tunas has been demonstrated by tagging studies (Joseph et al 1988).…”
Section: Discussionmentioning
confidence: 95%